Peran Mahasiswa dalam Memanfaatkan Teknologi pada Program Asistensi Mengajar di EL DE’OT Private Course - Darmawan, Kezia Eunike; Chamidah, Nur (Jurnal Teknologi Informasi untuk Masyarakat, 2025)
The Teaching Assistance Program is one of the implementations of the Merdeka Belajar Kampus Merdeka (MBKM) program, which aims to provide opportunities for students to participate in teaching and deepening their knowledge by becoming teachers, facilitators, tutors, trainers, or mentors in educational institutions within the community. This article documents the implementation of the Teaching Assistance Program by students of Universitas Airlangga at EL DE'OT Private Course. The students play the role of teaching assistants, creating teaching materials and being directly involved in the teaching and learning process in a non-formal institution in the form of private tutoring. In its implementation, students learn how to prepare teaching materials and teach using various teaching approaches, including fun learning, interactive PowerPoint, and exercises. It can be concluded that the program's objectives were successfully achieved, and the program provided various positive impacts for the students, the learners, and EL DE'OT Private Course as the institution where the teaching assistance took place. The students gained teaching experience, the learners acquired knowledge, and the institution involved obtained learning materials that could be used in the future.